Effect of CNC Interpolator Parameter Settings on Toolpath Precision and Quality in Corner Neighborhoods - Petráček P.; Fojtů P.; Kozlok T.; Sulitka M. (Multidisciplinary Digital Publishing Institute (MDPI AG), 2022)
Surface quality, machining time, and precision of the final workpiece are key criteria of optimization in CNC machining. These criteria are influenced by multiple factors, such as path interpolation, feed drive system settings, machine dynamics, and the manufacturing process. The properties of the output of the interpolator indirectly influence all subsequent phases of the machining process, thus influencing the quality of the end product. This paper focuses on the effects of interpolator settings on toolpath quality and precision in corner neighborhoods for the commercial Heidenhain iTNC interpolator. A novel method of toolpath quality evaluation suitable for interpolator output toolpaths is proposed, and the effect of multiple CNC parameters on toolpath quality and precision in corner neighborhoods is quantified based on results obtained on a testing toolpath and verified on a toolpath composed of linear segments only. Both toolpath quality and precision were found to depend primarily on the parameters of limit frequency, contour tolerance, and corner jerk settings with precision additionally depending on angle size. The results show that both toolpath quality and precision in corner neighborhoods can be successfully controlled by the corner jerk limit parameter settings. The presented methodology provides a practical guide for CNC parameter settings in Heidenhain interpolators aimed at predicting toolpath quality and precision in corner neighborhoods.
Keywords: toolpath quality; contour error; interpolator; CNC parameters; Heidenhain iTNC